ANALYSIS OF THE PREVALENCE OF DENTAL DISEASES AMONG CHILDREN AGED 12 YEARS - Дуда, Екатерина; Лебедь, Оксана (SWorldJournal, 2021)
The article presents the results of a survey of 203 students aged 12 years, including 111 boys and 92 girls (54% and 46%), as well as 41 children from the boarding school in Stryy, including 19 boys and 22 girls (46% and 54 %). The analysis of the results